From Classical To Calyspo: An Interview with Bahamian Composer and Conductor, Cleophas R. E. Adderley - Gangelhoff, Christine; Gibson, Ruebendero; Johnson, Crashan (International Journal of Bahamian Studies, 2011)
Transcript of an interview with Mr Adderley conducted March 23, 2011 in his office at the Ministry of Youth, Sports and Culture, Nassau, Bahamas. Mr Adderley is a pillar in the cultural development of the Bahamas as he is the founder and director of the Bahamas National Youth Choir.